Assessing and Improving Compressed Air Systems in Underground Mines (A Case Study in Iran) (Rudarsko-geološko-naftni zbornik, 2024)
Compressed air is one of the most common methods of energy transfer in industrial and mining systems. Compressed air has numerous applications in underground mines to ensure safety (ventilation fans), carry out extraction operations (compressed air equipment and machines), and manage technical services like dewatering and the operating of spare equipment. Therefore, it is necessary to investigate the compressed air supply systems in mines to assess the sufficiency of compressed air, reduce energy consumption, and lower operating costs. Considering the significance of utilizing compressed air in underground mines, it is essential to verify the adequacy of the flow rate and permissible pressure of compressed air for all mine air consumers. This requires proper design and adjustment of the compressed air distribution network. In this paper, the compressed air network in the main compressor house of the Qaleh-Zari copper mine in Iran was investigated. To achieve this goal, the compressed air consumption in various mining operation conditions was investigated and discussed after surveying the airflow transmission lines. The pressure drops in each line were estimated as well. Regarding the results, the airflow consumption in regular mining operations is about 36 cubic meters per second. The drop in air pressure within the network lines is below the permissible limit, but the overall pressure drop is significant. In this approach, practical adjustments such as changing the diameter of the pipes, increasing the airflow pressure, and utilizing local compressors near consumers' locations were proposed and investigated.